Corporate governance and financial performance of insurance firms in Kenya - Isaac Kibet Kiptoo (Taylor & Francis Group, 2021)
This study examined the relationship between corporate governance and the financial performance of insurance firms in Kenya over the period 2013–2018. The data were collected from 51 Insurance firms licensed to operate in Kenya as of 31 December 2018. Regression analysis was used and the results showed that corporate governance significantly affects the financial performance of insurance firms. In particular, the findings showed that board composition negatively and significantly affects financial performance. This implied that insurance firms with a bigger ratio of non-executive directors do not perform better than those with a less proportion of non-executive directors. Insurance firms should therefore reduce the ratio of non-executive directors in order to achieve better performance. The results also showed that board diversity positively and significantly affects financial performance. This implied that insurance firms with a bigger ratio of professional directors perform better than the firms with less proportion of professional directors to the board. Insurance firms should therefore engage more professional directors in order to provide professional guidance and enhance financial performance. The findings also indicated that board independence positively and significantly affects financial performance. This implied that firms with a bigger ratio of independent directors perform better than those with a smaller proportion of independent directors. Insurance firms should thus ensure that the board has an adequate number of independent directors in order to ensure independent or unbiased board decisions that will boost financial performance. The results also indicated that board size negatively and significantly affects financial performance. This implied that firms with bigger board sizes do not perform better than firms with smaller board sizes. The board size should thus be smaller to ensure efficiency and effectiveness of the board and better financial performance. This study concludes that proper corporate governance structure significantly affects the performance of a firm. Therefore, the study recommends that directors and other stakeholders should put in place appropriate governance structures in order to boost financial performance. Regulators and policymakers should also come up with policies and regulations that will ensure firms adopt appropriate governance structures to enhance performance. This study contributes to corporate governance literature by providing insight on the effect of corporate governance on performance from a developing country perspective. The study also provides an empirical examination of the effect of the various governance structures adopted by insurance firms and gives recommendations that can be utilized by policymakers in assessing and reviewing corporate governance policies. The study also gives recommendations to managers and other stakeholders regarding the board structure that can be adopted to boost the performance of a firm.